Pengaruh Penerapan Good Corporate Governance Terhadap Kinerja Perusahaan, dengan Komposisi Aset dan Ukuran Perusahaan sebagai Variabel Kontrol - Nadya Maretha; Anna Purwaningsih (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2013)
This research aims at revealing empirical proofs of Good Corporate Governance (GCG) implementation efect on frm performance. The samples are taken f rom frms listed in The Indonesian Institute for Corporate Governance (IICG) from 2007 - 2011 and Indonesian Stock Exchange 2006 – 2010. The numbers of the frms are 79. The independent variable is GCG measured with CGPI ranking score, meanwhile the dependent variable is the frms’performance proxied with ROE. The control variables are the composition of asset (asset) and frm’s size (size). Te hypothesis test employs multiple regression testing. The taken data are normally distributed and they fulfll classic assumption. The result shows that GCG positively infuence frms’ performance proxied with ROE. Despites, the two control variables, asset and size, statistically give positive infuence towards frms’performance.Keywords: asset, frms’ performance, firms’ size, good corporate governance (GCG), ROE